The Students’ Perception Toward the Implementation of Role Play Technique in Online-Based Speaking Learning - Noor Amartya Rusgiani (Journal of English Teaching and Linguistics Studies (JET Li), 2022)
The paper entitled “The Students’ Perception Toward the Implementation of Role Play Technique in Online-Based Speaking Learning” was purposed to describe students' perception of online-based speaking learning using role play techniques. This research was conducted at SMKN 1 Cibinong class XI TOI 1. This research used descriptive qualitative research guided by the research question "What are students' perception on the implementation of Role Play in an online speaking class?". The instruments used in this research were observation, questionnaires, and interviews. The results of this research indicate that most students have the same perception regarding the use of role play technique in online-based speaking learning. This is evidenced by the indicators used in this study, students’ understanding and students’ motivation. The use of this role play technique can improve students' understanding and motivation in learning speaking. Where students can learn to talk directly with the other person, it means students can practice their speaking fluency so that their speaking ability can improve. In addition, they are also motivated to learn, because in speaking learning using role play technique is more practice to speak, so they are very motivated to learn speaking using role play technique